Driving factors of open innovation adoption on MSMEs in Indonesia - P. Suliyanto, Weni Novandari,; Kartawan, M. (Opción, 2019)
This exploratory research aimed to identified basic dimensions which drive the open innovation implementation by MSMEs in Indonesia.The Analysis tools used in this research was Factor Analysis with varimax rotation.The analysis results showed there were 4 factors drivenMSMEs to do some cooperation with external parties in some activities in order to develop their own product. Those 4 factors are; deeper market insight orientation, improve capability orientation, expand network orientation andidea generated orientation. This finding can be used as a consideration for external parties who concern in MSMEs development.